LYRA, solar uv radiometer on the technology demonstration platform PROBA-2 - Stockman, Y; Hochedez, J.-F; Schmutz, W; BenMoussa, A; Defise, J.-M; Denis, F; D'Olieslaeger, M; Dominique, M; Haenen, K; Halain, J.-P; Koller, S; Koizumi, S; et al. (SPIE, 2017)
LYRA is a solar radiometer part of the PROBA 2 micro satellite payload. LYRA will monitor the solar irradiance in four soft X-Ray - VUV passbands. They have been chosen for their relevance to Solar Physics, Aeronomy and SpaceWeather: 1/ Lyman Alpha channel, 2/ Herzberg continuum range, 3/ Aluminium filter channel (including He II at 30.4 nm) and 4/ Zirconium filter channel. The radiometric calibration is traceable to synchrotron source standards. The stability will be monitored by on-board calibration sources (LEDs), which allow us to distinguish between potential degradations of the detectors and filters. Additionally, a redundancy strategy maximizes the accuracy and the stability of the measurements. LYRA will benefit from wide bandgap detectors based on diamond: it will be the first space assessment of revolutionary UV detectors. Diamond sensors make the instruments radiation-hard and solar-blind (insensitive to visible light) and therefore, make dispensable visible light blocking filters. To correlate the data of this new detector technology, well known technology, such as Si detectors are also embarked. The SWAP EUV imaging telescope will operate next to LYRA on PROBA-2. Together, they will provide a high performance solar monitor for operational space weather nowcasting and research. LYRA demonstrates technologies important for future missions such as the ESA Solar Orbiter.